INFORMATION SYSTEM FOR INVENTORY OF GOODS USING PROTOTYPE MODEL - Syahriani Syahriani; Basuki Basuki; Luthfi Indriyani (Jurnal Riset Informatika, 2021)
Inventory management is the most important activity, because if the inventory in the warehouse is not managed properly, it will allow a decrease in profits and loss of customers. PT Andalan Teknik Karetindo Putra Bangsa has weaknesses in its inventory management activities, where the presentation of the information is done manually, namely through the process of recording in a book, then transferred to the Speedsheet application. Sometimes the data submitted is inaccurate, that is, there are still errors regarding the stock of goods. In this research, we used a prototype software model.. Making this website is made to overcome these problems and to increase the effectiveness and efficiency of company performance. Where we make 2 level access rights, namely for warehouse staff and company leaders. With this website, warehouse staff can quickly and accurately find out the availability of goods and leaders can immediately find out the stock of goods available in the warehouse and can immediately print inventory reports without having to ask to the warehouse.